Islamic Religious Education Assistance In Communities Affected By Prostitution In Downstream Indragiri - Komariah, Nur; Ruhiat, Ruhiat; Suriyah, Suriyah; Murni, Dewi; Sabarudin, Sabarudin; Wijayanti, Sri (Jurnal Masyarakat Mengabdi, 2024)
This service is carried out to increase understanding of religion and the practice of Islam in the coastal communities of the Indragiri Hilir river, Tembilahan Kota Village, Tembilahan District, Indragiri Hilir Regency. The service method uses the Participatory Action Learning System (PALS) method, a method that emphasizes the activeness and participation of partners in the learning process in the form of prayer practices, reading the Koran and its application in daily life. The results of the service show that there is an increase in understanding and practice of the partner's religion. This can be seen from the increase in mastery of reading and the practice of the five daily prayers, the ability to read the Koran and the enthusiasm of partners in seeking work that is approved by Allah through agriculture. To empower communities affected by prostitution, there needs to be synergy between the government and ulama or intellectuals to empower partners to get out of this dark world. Empowerment is not only in the form of material such as social service programs in the form of the Family Planning Program (PKH), programs from education services such as the Smart Indonesia Card (KIP), health services such as the Healthy Indonesia Card (KIS) but is also supported by local government policies through localization closures. , and from the Ministry of Religion and Intellectual Services to make it easier for partners to get out of their dark zones.